Changes in Slight and Extreme Precipitation Events From 1963 to 2017 Over Northern Xinjiang, China - Li, Minggang; Zhao, Yong; Li, Yang; Zhou, Xin; Zhang, Shaobo (Frontiers in Earth Science, 2021)
We studied two types of precipitation event, slight rainfall (SR) and extreme rainfall (ER), using daily rainfall and mean temperature data from 25 stations in Xinjiang Province from 1963 to 2017. We discuss the statistical characteristics, linear trends, and temporal concentration of SR and ER events, and consider relationships between SR and ER events and daily mean temperature. The results show that SR events contribute strongly to the total annual number of rain days, and that ER events contribute strongly to the total annual rainfall. There is a notable downward (upward) trend in SR (ER) event frequency in northern Xinjiang, which means that the contribution of SR (ER) events to total annual rainfall amount has significantly declined (increased) over the 55 years. The trends in the annual number of rain days and in total annual rainfall amount have been opposite since the late 1990s because of the accelerated decline in SR event frequency and simultaneous increase in the annual rainfall amount from ER events. At an intra-annual scale, SR events are usually distributed through most months of the year, while ER events are usually concentrated in summer (JJA). In agreement with the frequency trends for SR and ER events, the intra-annual concentrations for SR and ER events have significantly increased and decreased, respectively, during the 55-year period. Distinct differences are found between the relationship of SR events to daily mean temperature and the relationship between ER event and daily mean temperature. The daily mean temperature for days with SR events is between –35°C and +34°C at stations in northern Xinjiang, and ranges from –21°C to +30°C for ER events. Regionally averaged curves for the change in SR and ER event frequency with temperature have bimodal and unimodal distributions, respectively. There is closer agreement between the trends for different daily mean temperatures and for SR event frequency than there is between the trends for different daily mean temperatures and for ER event frequency over recent decades. These results are helpful for improving the understanding of the characteristics and variability of rainfall in arid regions in the context of climate warming.